2019
DOI: 10.1002/ange.201901760
|View full text |Cite
|
Sign up to set email alerts
|

A Biocompatible Heterogeneous MOF–Cu Catalyst for In Vivo Drug Synthesis in Targeted Subcellular Organelles

Abstract: As at ypical bioorthogonal reaction, the coppercatalyzedazide-alkyne cycloaddition (CuAAC) has been used for drug design and synthesis.H owever,f or localized drug synthesis,i ti si mportant to be able to determine where the CuAACr eaction occurs in living cells.I nt his study,w e constructed ah eterogeneous copper catalyst on am etalorganic framework that could preferentially accumulate in the mitochondria of living cells.Our system enabled the localized synthesis of drugs through as ite-specific CuAACr eacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(15 citation statements)
references
References 70 publications
0
15
0
Order By: Relevance
“…Thus,i n2 019, this group developed ac atalyst based on aM OF support that holds and stabilizes ultrasmall copper(0) nanoparticles at their inner cavities (5-10 wt %). [37] Interestingly,b yd ecorating the resulting MOF-Cu particles with at riphenylphosphonium vector (MOF-Cu-TPP,F igure 5B), the authors showed that they can preferentially accumulate in the mitochondria of living cells, wherein they remaina ctive. As ar esult, this strategy allowed the mitochondria-localized generation of ar esveratrol-derived drug from their respective azide and alkynep recursors .…”
Section: Copper(i)-promoted Azide-alkyne Cycloaddition (Cuaac)mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus,i n2 019, this group developed ac atalyst based on aM OF support that holds and stabilizes ultrasmall copper(0) nanoparticles at their inner cavities (5-10 wt %). [37] Interestingly,b yd ecorating the resulting MOF-Cu particles with at riphenylphosphonium vector (MOF-Cu-TPP,F igure 5B), the authors showed that they can preferentially accumulate in the mitochondria of living cells, wherein they remaina ctive. As ar esult, this strategy allowed the mitochondria-localized generation of ar esveratrol-derived drug from their respective azide and alkynep recursors .…”
Section: Copper(i)-promoted Azide-alkyne Cycloaddition (Cuaac)mentioning
confidence: 99%
“…Heterogeneous Cu-based nanoconstructs for bioorthogonal CuAACs. Figure5Ba dapted with permission from ref [37]…”
mentioning
confidence: 99%
“…lysosomes, mitochondria and nucleus etc.) via multiple mechanisms (Chakraborty et al, 2018;Wang F. et al, 2019;Yuanjie Zhu and Yuanjie Zhu, 2019;Guo et al, 2020).…”
Section: Current Scenario Of Subcellular Drug Targetingmentioning
confidence: 99%
“…The reaction system developed various advantages such as the avoidance of the troublesome delivery process and non-specific distribution of obnoxious moieties, possibilities of multi-drug synthesis, and high biocompatibility etc. (Wang F. et al, 2019). Similarly, another functionalized colloidal nanoparticulate system with chemical and biochemical surface functionalization was developed, which took into account the recent concept of nanoprobes.…”
Section: Current Scenario Of Subcellular Drug Targetingmentioning
confidence: 99%
“…Beyond being an excellent protective matrix for biomolecules, a variety of applications have recently emerged from the biocatalysts-MOF interfac (Figure 1) For instance, the facile surface functionalization, [24] stimuli-responsive behavior, [25,26] and some enzyme-mimicking characteristics [27,28] of MOFs enable innovative applications of the engineering MOFs with enzymes for smart catalysis. Furthermore, their high biomolecule loading capacity, biodegradability, controlled release property, stimuli-responsive characteristics, and high biocompatibility in vitro and in vivo [29][30][31][32] are prone to be a versatile nanoplatform for biocatalysts delivery and catalytic nanomedicine. By integrating site-responsive materials (e.g.…”
Section: Introductionmentioning
confidence: 99%